Draft pronouncement - Lembaga Piawaian Perakaunan Malaysia (Kuala Lumpur : Lembaga Piawaian Perakaunan Malaysia, 2010)
Contains the exposure draft published by the International Accounting Standards Board (IASB). The proposals may be modified in the light of the comments received before being issued in final form as amendments to International Financial Reporting Standards (IFRSs).
Title from CD-ROM
Keywords: Financial statements -- Standards -- Malaysia; Accounting -- Standards -- Malaysia; Property -- Accounting -- Malaysia